ФУНКЦИЯНИНГ САТҲ ЧИЗИҚЛАРИ ВА ГРАДИЕНТ ВЕКТОР МАЙДОНЛАР - Байтураев, А.М.; Аслонов, Ж.О. (SCIENCE and SOCIETY, 2021)
The article studies the properties of vector fields and level lines of differentiable functions. It is known that in the study of mathematical models of physical processes in physics, the role of vector fields is irreplaceable. For example, when describing the motion of an object in a gravitational or magnetic field, the forces acting on it are specified using a vector field. Also, the study of the vortices of vector fields is one of the main methods in the study of the dynamics of flying bodies. When studying the statics of a particle in a static field, the object on which the particle stands consists of a sphere, and the sphere is the level surface of the differentiable function.